Sex and suicide: The curious case of Toll-like receptors. - Paulo A Navarro-Costa; Antoine Molaro; Chandra S Misra; Colin D Meiklejohn; Peter J Ellis (PLoS Biology, 2020)
During in vitro fertilisation (IVF), pharmacological activation of the murine X chromosome-encoded receptor proteins Toll-like receptor (TLR) 7 and TLR8 reportedly results in male-biased litters by selectively disrupting the motility of X-bearing sperm cells. Thus-in the context of agonist treatment during IVF-these receptors act as 'suicidal' segregation distorters that impair their own transmission to the next generation. Such behaviour would, from an evolutionary perspective, be strongly selected against if present during natural fertilisation. Consequently, TLR7/8 biology in vivo must differ significantly from this in vitro situation to allow these genes to persist in the genome. Here, we use our current understanding of male germ cell biology and TLR function as a starting point to explore the mechanistic and evolutionary aspects of this apparent paradox.